The effects of COVID-19 on the Spaniards’ reading habit - Magadán Díaz, Marta; Rivas García, Jesús Israel (University of Idaho Library, 2022)
The general objective of this work is to analyze the reading habit of Spaniards during and after COVID-19 confinement in the same period of the following year. The specific goals are: first, study the purpose of reading; second, know the type of book form read; third, assess the time spent reading during and after confinement and fourth, identify the motivating factors of reading during the COVID-19 isolation. This research used the online survey method through the Microsoft Forms tool and applied a simple random sampling to 1,251 Spanish citizens of legal age and residents in the country with social networks (Facebook, LinkedIn, or Twitter, together with WhatsApp) during May and June 2021. The main results obtained are: firstly, there is a direct and positive relationship between academic training and the habit of reading; secondly, the reading habit among women is higher than among men; thirdly, there is a direct and positive relationship between age and reading habit; fourthly, confinement has had a positive impact on reading habits; fifthly, it is evident that confinement has driven the online purchase of books; finally and sixthly, the paper book continues to have a leading position as a content medium, compared to other alternatives such as the electronic book or the audiobook.
Keywords: book; COVID-19; reading habit; Spain; Scopus